The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Ecws-3 2018
DOI: 10.3390/ecws-3-05804
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Geoinformatics and Hydrological Modelling-Based Approach for Effective Flood Management in the Jhelum Basin, NW Himalaya

Abstract: In the present study, using static land system parameters, such as geomorphology, land cover, and relief, we calculated the water yield potential (RP) of all the watersheds of the Jhelum basin (Kashmir Valley) using the analytical hierarchy process (AHP) based watershed evaluation model (AHP-WEM). The results revealed that among the 24 watersheds of the Jhelum basin, the Vishav watershed, with the highest RP, is the fastest water yielding catchment of the Jhelum basin followed by Bringi, Lidder, Kuthar, Sind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…It contributed to about 39.26% of worldwide natural disasters and caused USD 397.3 billion worth of damage between 2000 and 2014 [3,4]. Human activities such as urbanization, deforestation, and unplanned development all contribute towards the rise in the number of areas vulnerable to floods [3][4][5]. Moreover, the changing climate that has manifested the increase in the frequency of extreme precipitation events is also one of the primary forces behind the exacerbated flooding problem [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It contributed to about 39.26% of worldwide natural disasters and caused USD 397.3 billion worth of damage between 2000 and 2014 [3,4]. Human activities such as urbanization, deforestation, and unplanned development all contribute towards the rise in the number of areas vulnerable to floods [3][4][5]. Moreover, the changing climate that has manifested the increase in the frequency of extreme precipitation events is also one of the primary forces behind the exacerbated flooding problem [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive flood management strategy requires an understanding of its underlying causes by assessing the physio-climatic and hydrodynamic parameters as well as damage and exposure indices related to socioeconomic and ecological parameters [3][4][5]12]. The overall output of this exercise is finally the calculation of the flood risk that integrates hazard and vulnerability in assessing the latter's accumulation and propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after the devastating flood of September 2014, which left nearly 3.5% geographical area of the valley submerged and killing nearly 300 people, there has been no implementation of an operational flood forecasting system in the region. Although some studies for simulation and prediction of floods have been conducted using neural networks (Tabbussum and Dar 2021), statistical approaches (Parvaze et al 2021), hydrological models (Meraj et al 2018) and other soft computing techniques (Himayoun et al 2020), real time flood forecasting has yet not been implemented in the basin. The key component of the study is the use of a combination of hydrological and hydraulic model, on the river basin using open-source, geospatial, meteorological and hydrological information.…”
Section: Introductionmentioning
confidence: 99%
“…Geomorphic studies of some watersheds have been analyzed using various geospatial techniques which revealed that Kashmir Valley is highly susceptible to environmental hazards such as erosion, landslides, and floods due to its complex topography and perplexed geography (Gull et al 2017;Rather et al 2017;Meraj et al 2018). Lidder watershed, being one of the biggest watersheds of Kashmir Valley, needs continuous monitoring and proper assessment for effective management of its land and water resources.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%